Glove-related disorders among the phlebotomist, 2 case studies of occupational health problem - Wiwanitkit, Viroj (Srinagarind Medical Journal, 2013)
Objective : To present and discuss two case studies of gloves-related disorder among the phlebotomists. Case summary : The first case was a female health card worker in the laboratory unit consulted the physician with the complaint of skin lesion on her hands. From further history taking, she notified usage of rubber gloves. The wearing test patient was positive. The diagnosis for this case was glove-related skin disorder. The second case was a patient presented with the complaint of rhinorrhea, sneezing and itching at face after practices his laboratory work. He was advised to change the gloves to powder free gloves. The his symptoms were improved. This patient was diagnosed to have respiratory hypersensitivity. Discussion : Wearing gloves is an important item according to universal precautions. Glove-related disorders can be found among the phlebotomists. Gloves-related allergy is a common disorder can be occurred in blood collection procedure. The wide spectrum of allergic manifestation including contact allergy, rhinitis, asthma and acute allergic attack are mentioned. Some allergies occur suddenly, the other presented as a long-term effect. To diagnose this disorder is not difficult but sometimes overlooked. Although the described allergies is not frequently detected but awareness is important. Selection of allergen free instrument for venipuncture practice is recommended. Key Words : glove, phlebotomist